Public forms of positioning of the coordinating center of muslims of the North Caucasus in problematic situations of public relations - I. D. Ibragimov (Современная наука и инновации, 2025)
The article is devoted to the activities of the Coordinating Center of Muslims of the North Caucasus as a subject of Russian civil society in the framework of the socialization of Islam. The significant directions of the functioning of this religious organization, which have a public content, are highlighted. Such a form of activity as the preparation of appeals and statements is emphasized. The effectiveness of this form is determined by its publicity, targeting, efficiency, as well as socially significant meaning. A content analysis of some appeals and statements is carried out, which makes it possible to establish the inclusion of their plots, ideas and lexical resources in the socio-political processes of modern Russia.